Differentiating low- and high-proliferative soft tissue sarcomas using conventional imaging features and radiomics on MRI - Schmitz, Fabian; Voigtländer, Hendrik; Strauss, Dimitrios; Schlemmer, Heinz-Peter; Kauczor, Hans-Ulrich; Jang, Hyungseok; Sedaghat, Sam (BMC cancer, 2024)
Soft-tissue sarcomas are rare tumors of the soft tissue. Recent diagnostic studies mainly dealt with conventional image analysis and included only a few cases. This study investigated whether low- and high-proliferative soft tissue sarcomas can be differentiated using conventional imaging and radiomics features on MRI.
Gesehen am 06.11.2025